Tackling marine pollution in the blue economy: Synergies between wastewater treatment technologies and governmental policies - Setyo Budi Kurniawan; Ali Roziqin; Azmi Ahmad; Mahasin Maulana Ahmad; Benedicta Dian Alfanda; Dwi Sasmita Aji Pambudi; Nor Sakinah Mohd Said; Peer Mohamed Abdul; Muhammad Fauzul Imron (Marine Pollution Bulletin, 2026)

Orangutan population monitoring methods: Strengths, challenges, and opportunities - Valentino Koloski; Marijke van Kuijk; Muhammad Ali Imron; Hero Marhaento; Indah Sartika Sari; Fenky Wirada; Joeri A. Zwerts (Biological Conservation, 2025)

Quantifying market prevalence, abundance, and suitable habitats of bulbuls in Java, Indonesia - Muhammad Ali Imron; Muhammad Tafrichan; Vincent Nijman; K. Anne-Isola Nekaris; Marco Campera; Febrian Edi Nugroho; Swiss Winasis; Riri Retnaningtyas; George A. Gale; Wanlop Chutipong (Biological Conservation, 2025)

Cases of oil spills in the Indonesian coastal area: Ecological impacts, health risk assessment, and mitigation strategies - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Ali Roziqin; Dwi Sasmita Aji Pambudi; Benedicta Dian Alfanda; Mahasin Maulana Ahmad; Fatmalia Khoirunnisa; Rizka Andriani Mahmudah; Rizkiy Amaliyah Barakwan; Hajjar Hartini Wan Jusoh; Hafizan Juahir (Regional Studies in Marine Science, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

An agent-based model of agricultural land expansion in the mountain forest of Timor Island, Indonesia - Eko Pujiono; Ronggo Sadono; Muhammad Ali Imron; Sutomo; Hedi Indra Januar; Relawan Kuswandi; Hery Kurniawan; Etik Erna Wati Hadi; Muhammad Hadi Saputra; Izhamil Hidayah; Nida Humaida; Jalma Giring Sukmawati; et al. (Journal of Mountain Science, 2024)

Wildlife trade and the establishment of invasive alien species in Indonesia: management, policy, and regulation of the commercial sale of songbirds - Vincent Nijman; Ahmad Ardiansyah; Penthai Siriwat; Hélène Birot; Swiss Winnasis; Evros Damianou; Muhammad Ali Imron; Abdullah Langgeng; Beth Lewis; K. Anne-Isola Nekaris (Biological Invasions, 2022)
In Southeast Asia, mynas (genus Acridotheres ) are amongst the most invasive bird species. Information is largely lacking as to where they have established themselves. The spread of invasive, non-native mynas is partially or largely driven by the massive trade in these species as songbirds. While preventing unintentional introductions early is the most effective management option, these species continue to be traded in bird markets throughout the region. We focus on the trade of native and non-native species of mynas, and the establishment of non-native mynas on the Indonesian islands of Java, Bali, and Lombok. Between 2016 and 2019, through field surveys and use of citizen science data (e.g., Burungnesia, iNaturalist, birding reports), we assessed where non-native mynas have been recorded in the wild on these three islands; through bird market surveys we established in which cities these birds are traded. We recorded common myna in Yogyakarta, one of our three survey areas. Combining all records, the areas where alien invasive mynas are established are Greater Jakarta (common and jungle myna), Yogyakarta (common myna), Bali (common and bank myna) and Lombok (common and Javan myna). Two-thirds of the records come from farmlands, home gardens and urbanised areas. In the bird markets, we recorded ~ 23,000 mynas of five species for sale, with Greater Jakarta, Bali and Lombok standing out as areas with high numbers of potentially invasive alien species offered for sale. Restrictions on the sale of wild-caught birds are not adhered to. Well-intended policies concerning the breeding and sale of legally protected species, whereby 10% of the stock is bred to be released in the wild, exacerbate the risk of the establishment of non-native species. We surmise that one of the most effective ways to reduce the risk of the accidental or deliberate release of potentially invasive alien mynas (and indeed other birds) into the wild is for governments and conservationists to work more closely with the retailers who hold the key to informing and educating consumers.

Abundance and richness of invertebrates in shade-grown versus sun-exposed coffee home gardens in Indonesia - Marco Campera; Budiadi Budiadi; Tomáš Bušina; Baladzuri Hafizh Fathoni; Janine Dermody; Vincent Nijman; Muhammad Ali Imron; K. A. I. Nekaris (Agroforestry Systems, 2022)
Complex agroforestry systems are suggested as a possible solution to reduce the effects of deforestation in the tropics while enhancing the livelihoods of local human populations. Coffee ( Coffea spp.) is one of the most important commodity crops in the world that can easily be cultivated in complex agroforestry systems. Coffee agroforestry systems usually sustain higher biodiversity levels than sun-exposed fields while keeping similar levels of productivity considering the several benefits of growing coffee under a complex system. We aim to explore the richness and abundance of invertebrates in coffee home gardens in West Java, Indonesia by comparing 14 sun-exposed and 14 shade-grown gardens. We collected data in March/April 2019 via pitfall traps, pan traps, and beating tray in each field. We ran generalised linear models to assess whether the number of species and the number of individuals of insects differed between sun-exposed vs. shade-grown coffee gardens, and tested associations between main taxa. Overall, there was no difference in the richness (sun-exposed: 19.86 ± SE1.19; shade-grown: 19.71 ± SE1.19; Z-value = 0.12, p value = 0.904) and abundance (sun-exposed: 141.93 ± SE 3.18; shade-grown: 139.93 ± SE3.16; Z-value = 0.35, p value = 0.706) of invertebrates in coffee gardens, although taxa specific differences were present. Sun-exposed fields had a higher abundance of invertebrates considered as pests (Blattodea: Rhinotermitidae, Ectobiidae; Coleoptera: Scarabaeidae, Lycidae and Tenebrionidae; Diptera: Anisolabididae, Drosophilidae and Sarcophagidae). Camponotus spp. were the most dominant ants in shade-grown gardens while Dolichoderus spp. and Myrmicaria spp. were more abundant in sun-exposed gardens. Despite the fact that sun-exposed coffee fields registered higher abundance of invertebrate pests than shade-grown coffee fields, the richness of invertebrates did not substantially vary between sun-exposed and shade-grown coffee, suggesting that the matrix of gardens offers advanced ecosystem services. It is important to keep the complexity of agroforestry systems that provide key habitats for biodiversity.

The sticky tasty: the nutritional content of the exudativorous diet of the Javan slow loris in a lowland forest - Tungga Dewi; Muhammad Ali Imron; Ganis Lukmandaru; Katherine Hedger; Marco Campera; K. A. I. Nekaris (Primates, 2022)

Thirty years of trade data suggests population declines in a once common songbird in Indonesia - Boyd T. C. Leupen; Lalita Gomez; Chris R. Shepherd; K. Anne-Isola Nekaris; Muhammad Ali Imron; Vincent Nijman (European Journal of Wildlife Research, 2020)

Assessment of causes and future deforestation in the mountainous tropical forest of Timor Island, Indonesia - Eko Pujiono; Ronggo Sadono; Hartono; Muhammad Ali Imron (Journal of Mountain Science, 2019)

A novel application of cultural consensus models to evaluate conservation education programs - K.A.I. Nekaris; Sharon McCabe; Denise Spaan; Muhammad Imron Ali; Vincent Nijman (Conservation Biology, 2018)
Conservation professionals recognize the need to evaluate education initiatives with a flexible approach that is culturally appropriate. Cultural‐consensus theory (CCT) provides a framework for measuring the extent to which beliefs are communally held and has long been applied by social scientists. In a conservation‐education context, we applied CCT and used free lists (i.e., a list of items on a topic stated in order of cultural importance) and domain analysis (analysis of how free lists go together within a cultural group) to evaluate a conservation education program in which we used a children's picture book to increase knowledge about and empathy for a critically endangered mammal, the Javan slow loris ( Nycticebus javanicus ). We extracted free lists of keywords generated by students ( n = 580 in 18 schools) from essays they wrote before and after the education program. In 2 classroom sessions conducted approximately 18 weeks apart, we asked students to write an essay about their knowledge of the target species and then presented a book and several activities about slow loris ecology. Prior to the second session, we asked students to write a second essay. We generated free lists from both essays, quantified salience of terms used, and conducted minimal residuals factor analysis to determine presence of cultural domains surrounding slow lorises in each session. Students increased their use of words accurately associated with slow loris ecology and conservation from 43% in initial essays to 76% in final essays. Domain coherence increased from 22% to 47% across schools. Fifteen factors contributed to the domain slow loris. Between the first and second essays, factors that showed the greatest change were feeding ecology and slow loris as a forest protector, which increased 7‐fold, and the humancentric factor, which decreased 5‐fold. As demonstrated by knowledge retention and creation of unique stories and conservation opinions, children achieved all six levels of Bloom's taxonomy of learning domains. Free from the constraints of questionnaires and surveys, CCT methods provide a promising avenue to evaluate conservation education programs.

The Influence of Agroforestry and Other Land-Use Types on the Persistence of a Sumatran Tiger (Panthera tigris sumatrae) Population: An Individual-Based Model Approach - Muhammad Ali Imron; Sven Herzog; Uta Berger (Environmental Management, 2011)